Sustainable Development Strategy on Poultry Industry in Indonesia - Saptana Saptana; Rahmat Fadhil; Atika Dyah Perwita (Prodi Hukum Ekonomi Syariah Fakultas Agama Islam Universitas Muhammadiyah Purwokerto, 2020)
Development of poultry industry that had been running in Indonesia which more emphasized in economic growth aspect, on one side has succeeded in increasing production, but on the other side it caused negative impact toward business and environmental sustainability. A new paradigm reorientation of poultry industry development was needed in terms of direction, strategy and policy. This paper aimed to study the success and the failure of poultry industry development by conventional approach, paradigm of sustainable poultry industry development, concept and implementation of integrated business partnership, and future perspective. The results of this study showed that the development of poultry industry by conventional approach had generated negative impact toward business stability and sustainability, also toward environmental sustainability. The paradigm of sustainable poultry industry development could be used as an alternative strategy in improving farmers welfare while maintaining environmental sustainability. This paradigm could work well if it was integrated with an integrated business partnership strategy from upstream to downstream. In order to support this effort, consolidation of poultry industry institutions from upstream to downstream was required, so that integration of product processes and between business people could be achieved.